Pelatihan Penyusunan Jurnal Penelitian Pendidikan Bagi Guru Sekolah Dasar Kecamatan Punggur Lampung Tengah - Muncarno; Nelly Astuti; Rapani; Siska Mega Diana (Jurnal Pengabdian Masyarakat Ilmu Pendidikan, 2022)
The purpose of this training is to understand and know about what and how an Educational Research Journal is and understand the preparation of an Educational Research Journal for elementary school teachers in Kotagajah Subdistrict, Central Lampung. This training uses the lecture method, question and answer method and the method of giving examples. Sources of research data are teachers in elementary schools throughout Kotagajah district, Central Lampung, totaling 20 people. The result of this training was that it was able to produce 5 drafts of writing an Educational Research Journal which was followed up with presentation activities in order to get input from various parties and the teachers felt they had gained the knowledge, skills and or experience they really needed.